Desenvolvimento profissional de professores que lecionam matemática no ensino fundamental : possibilidades a partir da reflexão sobre os erros dos alunos - Costa, José Roberto (2014)
The reflection on the need to overcome traditional practices of continuing education raised questions which led us to conduct this research. The error made by the student during the learning process has been taken as the starting theme for reflection with teachers participating in the research because we consider it would enable teachers to better understand difficulties in their profession. Our aim was to investigate the possibilities to establish a professional development process in a group of six teachers of mathematics based on their reflection on the mistakes made by students of the 6th year of elementary school. Initially, a literature study was carried out with the purpose of rescuing the literature regarding continuing education for teachers, the teacher's professional development and analysis of students' errors. The present research is a qualitative one and had as investigation tools: class observation, before and during the reflective process; structured interview conducted before, during and after the reflecting process; and meetings with teachers within a continuing education proposal based on the error analysis, which involved in-service teachers with a dynamic exchange of experiences and reflections on students' errors. The analysis of the education process was grounded on the teachers' speech and the recordings of the classes observed, which allowed us to identify and discuss four kinds of phenomena: reasons for students make mistakes; between the speech and the action; the education and the classroom; the importance of shared experience. The data analysis suggests that five out of six research participants are going through a changing process of their understanding about the errors and the necessary action to be taken in the classroom to treat them more conveniently and thoughtfully. The analysis of the lessons observed showed that half of the teachers presented advances concerning the different treatment toward the mistakes made by students. Although the style of correction activities, most of the time, is still traditional, it involved more questioning than previously, providing further discussions between the students and the teacher. As the process of professional development is continuous, it tends to improve even more with the continuity of meetings and joint reflection.